Evolutionary drivers of seasonal plumage colours: colour change by moult correlates with sexual selection, predation risk and seasonality across passerines. (23rd August 2019) - McQueen, Alexandra; Kempenaers, Bart; Dale, James; Valcu, Mihai; Emery, Zachary T.; Dey, Cody J.; Peters, Anne; Delhey, Kaspar
Abstract: Some birds undergo seasonal colour change by moulting twice each year, typically alternating between a cryptic, non‐breeding plumage and a conspicuous, breeding plumage ('seasonal plumage colours'). We test for potential drivers of the evolution of seasonal plumage colours in all passerines ( N = 5901 species, c. 60% of all birds). Seasonal plumage colours are uncommon, having appeared on multiple occasions but more frequently lost during evolution. The trait is more common in small, ground‐foraging species with polygynous mating systems, no paternal care and strong sexual dichromatism, suggesting it evolved under strong sexual selection and high predation risk. Seasonal plumage colours are also more common in species predicted to have seasonal breeding schedules, such as migratory birds and those living in seasonal climates. We propose that seasonal plumage colours have evolved to resolve a trade‐off between the effects of natural and sexual selection on colouration, especially in seasonal environments.